b-2-6b=36

Simple and best practice solution for b-2-6b=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for b-2-6b=36 equation:



b-2-6b=36
We move all terms to the left:
b-2-6b-(36)=0
We add all the numbers together, and all the variables
-5b-38=0
We move all terms containing b to the left, all other terms to the right
-5b=38
b=38/-5
b=-7+3/5

See similar equations:

| 1/11y+3=-1 | | 6+s=-9 | | -84+14x=3x+98 | | 4+2(8x-11)=1-7(10x-5) | | 3w+6+w=4w+4+10 | | 8x+3-6x=19 | | (x+9)^2+64=0 | | 8+13t-7=8t+9-3t | | ++7=-6x | | 2x+4x+150+5=180 | | 42=2x+9 | | -5r/8=-25 | | 5x-1x-18=6-2x+-30 | | n/22=-22 | | n+(n-12)=40 | | 4(m-1)=8(m+1)+3 | | 9g/4=-27 | | 3x*7=20 | | (2x+15)=65 | | 2x-6x-8=-4x+7-8 | | 3w-41=-7(w+3) | | 1n+4=18 | | 9n5+9=90 | | -5(3b+12)=-3b-5(b+12) | | 3(x+3)=7(x-5) | | 3x-9=6x+7 | | (2x+15)+65=180 | | 9.7-0.5x=8.7 | | 10x-90=-90 | | (p×p)+8p-82=0 | | 39.99+.45a=44.99+0.4 | | b/2+5b/9-8/6=b+2/6 |

Equations solver categories